Revisiting food and nutrition security: A comprehensive overview - Ecker, Olivier; Breisinger, Clemens (2013)
The modest progress in reducing malnutrition over the past two decades and the severe impacts of recent food crises have re-ignited a debate on new ways for improving food and nutrition security. This paper contributes to the discussion by synthesizing the pertinent literature and presenting an innovative framework that may help identifying and designing promising pathways to food security and improved nutrition. The framework links the complex interactions of factors at the macro and micro levels and shows how external shocks such as global food price spikes and natural disasters as well as interventions in form of policies and programs affect the availability of food, people's access to it, and the resulting nutritional status of individuals.